Ciência, política e biodiversidade : o Livro vermelho das espécies ameaçadas de extinção da fauna de Minas Gerais (1989-1998) - Gabriel Schunk Pereira (2021)
The present work intends to discuss the elaboration process of the Red Book of Endangered Species of Fauna of Minas Gerais, published by the Biodiversitas Foundation, in 1998. The publication of lists and red books of threatened species began in the 1960s with the International Union for Conservation of Nature. This type of scientific literature is one of the mechanisms that constitute biodiversity conservation strategies, proposing to indicate endangered species in order to guide conservation policies. Throughout the dissertation, we aim to clarify how the production and publication of this work is the result of the intersection between the scientific work of some conservationist biologists from Minas Gerais and the political activities of these same individuals as environmental activists. Based on dialogues established with the history of science and environmental history and based on some concepts by Ludwik Fleck (2010), we show how these characters struggled to insert in the State Constitution of Minas Gerais the constitutional duty of the state to draw up its lists of threatened species. Then, we seek to understand how this scientific enterprise was structured in scientific collectives and how a certain group of scientists defined a methodology to establish, as a scientific fact, which species were threatened with extinction in the state. We indicate how these same actors have been circulating through different collectives and directly involved in the constitution of two specific collectives, the master's course in Ecology, Conservation and Wildlife Management, in which professionals were trained oriented to a certain way of conceiving conservation Biodiversitas Foundation, the institution that produced the list and state red book. We conclude that the Minas red book is an expression shared by scientists who are part of a collective on the state of conservation of species of the Minas Gerais fauna and, based on categories and criteria established by the IUCN, they developed a methodological guide that, first, reflected an effort to objectify objectivity, making the production of the list and red book, from processes of mathematization and quantification, something less subjective, and, second, it defined one way and not another to produce this type of literature. Finally, although presented as the result of a scientific procedure and, therefore, neutral, the Minas red book is a political instrument, which presents a specific way of thinking about the management of Minas Gerais' biodiversity, and capable of being mobilized by the group that elaborated it. It is evident, then, how the political performance of this group of environmentalists, in the social sphere, is intrinsically related to their scientific work, and it is not possible to understand the Minas red book without thinking about the relationship and mutual influence between science and politics.